Is the Central Sensitization Inventory (CSI) associated with quantitative sensory testing (QST)? A systematic review and meta-analysis - Neblett, Randy; Sanabria-Mazo, Juan P.; Luciano, Juan V.; Mirčić, Milica; Čolović, Petar; Bojanić, Marija; Jeremić-Knežević, Milica; Aleksandrić, Tijana; Knežević, Aleksandar (Neuroscience and biobehavioral reviews, 2024)
Central sensitization (CS) involves an amplification of neural processing within the central nervous system that can result in widespread pain patterns and hypersensitivity to stimuli. The Central Sensitization Inventory (CSI) and various quantitative sensory testing (QST) methods purport to assess clinical markers of CS. The purpose of this systematic review and meta-analysis was to summarize and quantify the associations between total CSI scores and QST measures from previous studies. A systematic search identified 39 unique studies that were deemed eligible for the systematic review and 33 studies for meta-analyses (with 3314 subjects and 154 effect sizes), including five QST modalities: conditioned pain modulation, temporal summation, pressure pain threshold, heat pain threshold, and cold pain threshold. The meta-analysis yielded statistically significant CSI-QST correlations in total subject samples for all five QST modalities. The strongest associations were identified between CSI scores and pain threshold testing, especially pressure pain threshold, in which 51% of effects sizes, from 29 studies and 3071 subjects, were determined to be in a medium to large range. •Significant correlations were found between CSI total scores and five separate QST modalities.•The strongest association was found between CSI total scores and pressure pain threshold testing.•Knee osteoarthritis had the strongest CSI and pressure pain threshold relationship.•No CSI and pressure pain threshold relationship was found in healthy control subjects.